2016
DOI: 10.3109/13880209.2015.1103756
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect ofArthrospira(Spirulina)platensisagainst kainic acid-neuronal death

Abstract: Context Arthrospira (Spirulina) platensis (SP) is a cyanobacterium which has attracted attention because of its nutritional value and pharmacological properties. It was previously reported that SP reduces oxidative stress in the hippocampus and protects against damaging neurobehavioural effects of systemic kainic acid (KA). It is widely known that the systemic administration of KA induces neuronal damage, specifically in the CA3 hippocampal region. Objective The present study determines if the SP sub-chronic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…36 Recent studies have shown Spirulina platensis reduces oxidative stress in the hippocampus and protects CA3 neurons against damaging of systemic kainic acid. 34 Spirulina platensis has different roles, such as anti-inflammatory, anti-oxidative, neuroprotective, and hepatoprotective properties. 20,31,32,35 Because of its neuroprotective and antioxidant properties, the findings of the present study suggest that the application of Spirulina platensis as a natural food supplement is useful to prevention the cognitive-behavioral impairment induced by stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Recent studies have shown Spirulina platensis reduces oxidative stress in the hippocampus and protects CA3 neurons against damaging of systemic kainic acid. 34 Spirulina platensis has different roles, such as anti-inflammatory, anti-oxidative, neuroprotective, and hepatoprotective properties. 20,31,32,35 Because of its neuroprotective and antioxidant properties, the findings of the present study suggest that the application of Spirulina platensis as a natural food supplement is useful to prevention the cognitive-behavioral impairment induced by stress.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 It has been reported that Spirulina reduces oxidative stress in the hippocampus and protects against damaging neurobehavioral effects of systemic kainic acid. 34 SP enhanced the beneficial effect of exercise on oxidative stress and lipid profiles in rats. 35 The antioxidant property of Spirulina is ascribed to phycocyanin component, which is a potent antioxidant.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Perez-Juarez, Chamorro, Alva-Sanchez, Paniagua-Castro, and Pacheco-Rosado (2016) have shown that administration of kainic acid induces neurodegeneration by causing neuronal damage in the CA3 hippocampal region which is reduced by supplementation of Spirulina. It was also demonstrated that supplementation of Spirulina reduces oxidative stress in the hippocampal region resulting in a neuroprotective effect (Hwang et al, 2011;Perez-Juarez et al, 2016).…”
Section: Cyanobacteria As a Neuroprotective Agentmentioning
confidence: 99%
“…Besides, antioxidant compounds, this microalga contain significant amounts of protein (more than 70%), long-chain polyunsaturated fatty acids (PUFA), vitamins and especially vitamin B12, as well as minerals like zinc, manganese, magnesium, selenium and iron [13]. Oral administration of S. platensis is reported to increase the cellular antioxidant capacity and glutathione levels in cells against iron-induced oxidative stress [14] and prevent cell death induced by increased free radicals [15][16][17].…”
Section: Introductionmentioning
confidence: 99%